2016
DOI: 10.1364/ol.41.000757
|View full text |Cite
|
Sign up to set email alerts
|

Scaled-model guidelines for formation-flying solar coronagraph missions

Abstract: Stray light suppression is the main concern in designing a solar coronagraph. The main contribution to the stray light for an externally occulted space-borne solar coronagraph is the light diffracted by the occulter and scattered by the optics. It is mandatory to carefully evaluate the diffraction generated by an external occulter and the impact that it has on the stray light signal on the focal plane. The scientific need for observations to cover a large portion of the heliosphere with an inner field of view … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…However, these defects would be purely mechanical, and it is probably easier to achieve a very good quality for the occulter itself, in comparison to what is required for the optics in the Lyot coronagraph. A comparison with an experimental approach would be of interest, as was reported by Landini et al (2016).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…However, these defects would be purely mechanical, and it is probably easier to achieve a very good quality for the occulter itself, in comparison to what is required for the optics in the Lyot coronagraph. A comparison with an experimental approach would be of interest, as was reported by Landini et al (2016).…”
Section: Resultsmentioning
confidence: 94%
“…Our results are therefore not comparable to their results. Finally, Landini et al (2016) presented an experimental study of the rejection of various external occulters, based on a reduced scale test bench.…”
Section: Introductionmentioning
confidence: 99%
“…Following this analysis, some hypotheses and parameters can be refined to better fit with the reality: 1-To consider real BTDF measurement of lenses in the µroughness scattering model 2-To consider a contamination model (following Mie theory) that will add to the µroughness scattering 3-To add the propagation of the diffraction as calculated in [9] to the final straylight irradiance 4-To consider a way to use the real diffraction profile and compute the generated straylight…”
Section: Resultsmentioning
confidence: 99%
“…The propagation of the diffraction itself through the ASPIICS instrument was not performed at this time, but the diffraction signal itself should be added to this comparison to get a full overview of the in-FoV straylight. This calculation is being made through a numerical model presented in [9] and [11].…”
Section: Icso 2018 International Conference On Space Opticsmentioning
confidence: 99%
“…Thus Landini et al (2010) and Landini et al (2011) compared the efficiency of linear segments of various occulters, and thick occulters were again found to be more efficient, with the advantage being about factor of two. Later, Landini et al (2016Landini et al ( , 2017a developed an analytical model and showed how an ASPIICS-size configuration can be rescaled to a laboratory size (linear scaling for distances, and quadratic scaling for thicknesses) so that the experiments would be representative. However, in this case, the intensity of the diffracted light can be measured only in the entrance aperture plane and not in the detector plane, as otherwise the remaining optical system would be scaled down to an unrealistic size.…”
Section: Discussionmentioning
confidence: 99%